2013
DOI: 10.1002/pola.26740
|View full text |Cite
|
Sign up to set email alerts
|

Steric hindrance effect on thermo-responsive behaviors of well-defined water-soluble semi-rigid polymers

Abstract: Three series of water-soluble semi-rigid thermo-responsive polymers with well-defined molecular weights based on mesogen-jacketed liquid crystal polymers, poly [bis(N-(2-hydroxypropyl) pyrrolidoneand poly[bis(N-hydroxypropyl pyrrolidone) 2-vinylterephthalate] (PHPPVTA) have been synthesized via reversible addition-fragmentation chain transfer polymerization. The steric hindrance effects on liquid crystalline property and thermo-responsive behaviors of semi-rigid water-soluble polymers (P(2-HPPVTA), P(1-M-2-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Therefore, tailoring and broadening the T g range of sugarbased polycarbonate materials would further enable their usage in fields such as stretchable and self-healing materials, 18 drug delivery vehicles, 19 and soft implants/scaffolds. 20 Variation of T g has been extensively studied for traditional linear polymers and dendrimers, where T g is shown to correlate with certain parameters, including molar mass, 21,22 chemical composition of the backbone, 23 steric hindrance of substituents, 24 side chain flexibility, 25 chain-end composition, 26 intermolecular interaction between polymer chains, 27 crosslinking density, 28 and dispersity. 29 Under the guidance of polymer physics, various methods have been utilized in tailoring T g .…”
mentioning
confidence: 99%
“…Therefore, tailoring and broadening the T g range of sugarbased polycarbonate materials would further enable their usage in fields such as stretchable and self-healing materials, 18 drug delivery vehicles, 19 and soft implants/scaffolds. 20 Variation of T g has been extensively studied for traditional linear polymers and dendrimers, where T g is shown to correlate with certain parameters, including molar mass, 21,22 chemical composition of the backbone, 23 steric hindrance of substituents, 24 side chain flexibility, 25 chain-end composition, 26 intermolecular interaction between polymer chains, 27 crosslinking density, 28 and dispersity. 29 Under the guidance of polymer physics, various methods have been utilized in tailoring T g .…”
mentioning
confidence: 99%
“…The low intensity and broad shape of the reflections indicate poor molecular packing and hence reduced interaction. So, from the aforesaid data, it is confirmed that compound 4.4 shows columnar nematic phase (N Col ), which is uncommon in the family of discotics.…”
Section: Resultsmentioning
confidence: 69%
“…Homo-PHIPPVTA is a type of mesogen-jacketed liquid crystal polymer (MJLCP). 44,46 In order to explore the liquid-crystalline behaviors of PNIPAm-b-PHIPPVTA, polarized light microscope (PLM) and one-dimensional wide angle X-ray diffraction (1D WAXD) were employed. The block copolymer samples were amorphous when the molecular weight is lower than a critical molecular weight of approximately 2.76 Â 10 4 g mol À1 for the N 43 bH x and 4.48 Â 10 4 g mol À1 for the N 151 bH x , respectively.…”
Section: Synthesis and Bulk Property Of The Block Copolymer Pnipamb-p...mentioning
confidence: 99%
“…PHIPPVTA separate from aqueous solution as the temperature exceeded cloud point due to the conguration transformation from hydrophilic soluble chains to hydrophobic collapsed domains. 44,46 Incorporation of more hydrophobic (lowering the LCST) comonomers (NIPAm) into homopolymer chains with unusual thermo-responsive properties resulted in the cloud point changes. 45 Herein, the rod-coil diblock copolymers with PHIPPVTA rod units and exible PNIPAm coil were precisely controlled to clarify the inuence of chain length and polymer composition on the thermo-responsive behavior.…”
Section: Solution Property Of the Block Copolymer Pnipam-b-phippvtamentioning
confidence: 99%
See 1 more Smart Citation